2014
DOI: 10.1155/2014/106049
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Thermal Response to Dry-Sauna Exposure in Healthy Subjects

Abstract: Dry-sauna is a strong thermal stimulus and is commonly used all over the world. The aim of this experiment was to comprehensively analyse cardiovascular and autonomic changes that result from an increase in core body temperature during sauna bath. The study included 9 healthy men with mean age 26.7 ± 3.0 years and comparable anthropomorphical characteristics. Each subject was exposed to one 15-minute session of dry-sauna treatment at 100°C and 30–40% humidity. The autonomic and baseline cardiovascular (i.e., h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In patients, simple approaches to transiently increase body temperature and metabolic rate could be vigorous exercise, which is difficult for patients, or dry sauna treatments (Hussain and Cohen, 2018). Dry saunas begin to raise core body temperature within 15 min (Zalewski et al, 2014). More aggressive approaches could involve pyrogen treatments, like LPS (lipopolysaccharide).…”
Section: How Could Changes To Body Temperature Help Constrain Cancer Cell Diversity and Adaptability To Facilitate Tumor Cell Extinction?mentioning
confidence: 99%
“…In patients, simple approaches to transiently increase body temperature and metabolic rate could be vigorous exercise, which is difficult for patients, or dry sauna treatments (Hussain and Cohen, 2018). Dry saunas begin to raise core body temperature within 15 min (Zalewski et al, 2014). More aggressive approaches could involve pyrogen treatments, like LPS (lipopolysaccharide).…”
Section: How Could Changes To Body Temperature Help Constrain Cancer Cell Diversity and Adaptability To Facilitate Tumor Cell Extinction?mentioning
confidence: 99%
“…In [6], the exposure to single sauna session led to a minor warming intervention with negligible effects on physiological strain where HR was reported to be increased from 65 to 106 bpm, while in [7] no data were collected during the sauna. In this study, a higher increment of mean HR (up to 133 bpm) in combination with the elevated mean core body temperature (up to 38.7 o C) suggests that repetitive exposures to sauna sessions induces internal thermal strain level meeting the criteria of severe whole-body hyperthermia level.…”
Section: Discussionmentioning
confidence: 99%
“…Bruce et al [6] reported that during a single sauna session HR and sympatho-vagal ratio increased significantly compared to pre-exposure. Zalewski et al [7] reported an increment in HR and sympatho-vagal ratio immediately after the exposure that lasted up to 3 hours later.…”
Section: Introductionmentioning
confidence: 98%
“…There is considerable evidence to suggest that sauna bathing can induce profound physiological effects [ 4 , 11 17 ]. Intense short-term heat exposure elevates skin temperature and core body temperature and activates thermoregulatory pathways via the hypothalamus [ 18 ] and CNS (central nervous system) leading to activation of the autonomic nervous system.…”
Section: Introductionmentioning
confidence: 99%